Global research status analysis of the association between aortic aneurysm and inflammation: a bibliometric analysis from 1999 to 2023 - Wang, Qiuguo; Chen, Guihuan; Qi, Zhen; Zeng, Yifan; Tan, Ling; Tang, Hao (Frontiers in Cardiovascular Medicine, 2023)
Aortic aneurysm is a chronic arterial disease that can lead to aortic rupture, causing severe complications and life-threatening risks for patients, and it is one of the common causes of death among the elderly. Increasing evidence suggests that inflammation plays an important role in the progression of aortic aneurysm. However, there is a lack of literature-based quantitative analysis in this field.Up to March 30, 2023, we collected 3993 articles related to aortic aneurysm and inflammation from the Web of Science Core Collection (WoSCC) database for bibliometric analysis. The collected literature data were subjected to visual analysis of regional distribution, institutions, authors, keywords, and other information using tools such as CiteSpace, VOSviewer, the R package "bibliometric," and online platforms.The number of publications in this research field has been steadily increasing each year, with the United States and China being the main contributing countries. Harvard University in the United States emerged as the most active and influential research institution in this field. Jonathan Golledge and Peter Libby were identified as the authors with the highest publication output and academic impact, respectively. Researchers in this field tend to publish their findings in influential journals such as the Journal of Vascular Surgery and Arteriosclerosis Thrombosis and Vascular Biology. "Abdominal aortic aneurysm," "giant cell arteritis," "arterial stiffness," and "smooth muscle cells" were identified as the hottest topics in the field of aortic aneurysm and inflammation. In terms of keyword cooccurrence analysis, " Clinical relevant studies of AA " (red), "Inflammatory activation" (green), "Inflammatory mechanisms related to pathogenesis" (dark blue), "Cytokines" (yellow), "Risk factors" (purple), and "Pathological changes in vascular wall" (cyan) formed the major research framework in this field. "Inflammation-related pathogenesis" and "inflammation activation" have emerged as recent hot research directions, with "monocytes," "progression," and "proliferation" being the prominent topics.This study provides a comprehensive analysis of the knowledge network framework and research hotspots in the field of aortic aneurysm and inflammation through a literature-based quantitative approach. It offers valuable insights to guide scholars in identifying meaningful research directions in this field.